SIMULASI PENDUGAAN LONGSOR: PENGARUH INTENSITAS HUJAN PADA TANAH DENGAN TEKSTUR DAN KANDUNGAN BAHAN ORGANIK YANG BERBEDA - Nur Fadillah Aunur Rofiq; Sri Rahayu Utami; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2022)
Natural factors and human actions can cause landslides. Natural factors include high rainfall intensity and mountainous areas or hills with steep slopes. Human actions that can cause landslides are land conversion and inappropriate land management. This study aimed to explore the effect of rain intensity on soils with different textures and organic matter content. The landslide simulation study was conducted at the Agro Techno Park and Experimental Field, Faculty of Agriculture, Brawijaya University. This study used an acrylic box (size 100 cm x 50 cm x 75 cm) and aluminium plate as a base, which was adjusted to a slope of 50. There were eight treatment combinations consisting of three factors: soil texture (silty and clayey), rainfall intensity (70 mm hour-1 and 120 mm hour-1 ), and organic matter application (without and with organic matter application). The variables measured were landslide duration and volume. The results showed that the duration and volume of landslide materials are largerly influenced by rainfall intensity. Adding organic matter to the soil at any rainfall intensity may decrease landslide duration and volume by half compared to without organic matter application. Among the three factors examined (soil texture, organic matter application and rainfall intensity), rainfall intensity seems to be the most determining factor in landslide duration and volume.